Cytochrome P450 mono‐oxygenase CYP703A2 plays a central role in sporopollenin formation and ms5ms6 fertility in cotton. Issue 10 (15th September 2022) - Ma, Huanhuan; Wu, Yuanlong; Lv, Ruiling; Chi, Huabin; Zhao, Yunlong; Li, Yanlong; Liu, Hongbo; Ma, Yizan; Zhu, Longfu; Guo, Xiaoping; Kong, Jie; Wu, Jianyong; et al.
ABSTRACT: The double‐recessive genic male‐sterile ( ms ) line ms5 ms6 has been used to develop cotton ( Gossypium hirsutum ) hybrids for many years, but its molecular‐genetic basis has remained unclear. Here, we identified the Ms5 and Ms6 loci through map‐based cloning and confirmed their function in male sterility through CRISPR/Cas9 gene editing. Ms5 and Ms6 are highly expressed in stages 7–9 anthers and encode the cytochrome P450 mono‐oxygenases CYP703A2‐A and CYP703A2‐D. The ms5 mutant carries a single‐nucleotide C‐to‐T nonsense mutation leading to premature chain termination at amino acid 312 (GhCYP703A2‐A 312aa ), and ms6 carries three nonsynonymous substitutions (D98E, E168K, and G198R) and a synonymous mutation (L11L). Enzyme assays showed that GhCYP703A2 proteins hydroxylate fatty acids, and the ms5 (GhCYP703A2‐A 312aa ) and ms6 (GhCYP703A2‐D D98E, E168K, G198R ) mutant proteins have decreased enzyme activities. Biochemical and lipidomic analyses showed that in ms5 ms6 plants, C12–C18 free fatty acid and phospholipid levels are significantly elevated in stages 7–9 anthers, while stages 8–10 anthers lack sporopollenin fluorescence around the pollen, causing microspore degradation and male sterility. Overall, our characterization uncovered functions of GhCYP703A2 in sporopollenin formation and fertility, providing guidance for creating male‐sterile lines to facilitate hybrid cotton production and therefore exploit heterosis for improvement of cotton. Abstract : Cloning the two causal genes for double‐recessive genic male‐sterile cotton line ms5 ms6 revealed that the mutants lack lauric acid hydroxylation activity, which causes a failure of sporopollenin formation, leading to defective pollen walls and male sterility in ms5ms6 plants.